Konsumsi Informasi Politik Gen Z di TikTok: Studi Kasus Isu Tunjangan Tempat Tinggal DPR - Aurelia, Frisca; Candraningrum, Diah Ayu (Kiwari, 2025)
The development of technology and social media has brought changes to information consumption patterns, especially among Generation Z who tend to prefer short, fast, and easily accessible content. TikTok, a platform that has grown rapidly in Indonesia, is no longer limited to functioning as an entertainment medium but has also become a space for disseminating information, including political issues such as the controversy over the housing allowance of the House of Representatives (DPR). This study analyzes the political information consumption patterns of Generation Z on TikTok using the Uses and Gratifications theory and Information Seeking Gratifications. This research employs a qualitative approach through in-depth interviews and digital observation, with the findings validated using the member check technique to ensure data accuracy. The results show that Generation Z’s political information consumption patterns are shaped by TikTok’s algorithm and the characteristics of short-form content that are easily absorbed. Although the understanding gained tends to be basic, this pattern effectively motivates Generation Z to actively seek more in-depth information. The study emphasizes that TikTok is effective in shaping young people’s political understanding, despite various challenges related to accuracy and information quality. Perkembangan teknologi dan media sosial membawa perubahan dalam pola konsumsi informasi, khususnya pada kalangan Gen Z yang cenderung menyukai konten singkat, cepat dan mudah diakses. TikTok, sebuah platform dengan perkembangan yang sangat pesat di Indonesia kini tidak lagi berperan sebatas sebagai media hiburan melainkan juga sebagai wadah penyebaran informasi, termasuk isu politik, seperti kontroversi tunjangan tempat tinggal DPR. Penelitian ini menganalisis pola konsumsi informasi politik Gen Z di TikTok dengan menggunakan teori Uses and Gratifications dan Information Seeking gratifications. Penelitian ini menerapkan pendekatan kualitatif berupa wawancara mendalam dan observasi digital, hasil temuan kemudian divalidasi dengan teknik member check untuk memastikan akurasi data. Hasil penelitian memperlihatkan pola konsumsi informasi politik Gen Z dibentuk oleh algoritma TikTok dan karakteristik konten singkat yang mudah diterima. Meskipun pemahaman yang diperoleh berupa pemahaman yang mendasar terkait sebuah isu, pola ini efektif memberikan motivasi bagi Gen Z untuk aktif mencari sebuah informasi yang lebih mendalam. Penelitian ini menegaskan TikTok yang efektif membentuk pemahaman politik generasi muda dengan berbagai tantangan akurasi serta kualitas informasi yang muncul.